Making community-supported agriculture accessible to low-income families: findings from the Farm Fresh Foods for Healthy Kids process evaluation. Issue 3 (15th September 2020) - Garner, Jennifer A; Jilcott Pitts, Stephanie B; Hanson, Karla L; Ammerman, Alice S; Kolodinsky, Jane; Sitaker, Marilyn H; Seguin-Fowler, Rebecca A
Abstract: A randomized trial of Farm Fresh Foods for Healthy Kids (F3HK) was initiated across 4 states and 12 farms to test whether cost-offset community-supported agriculture (CO-CSA) could improve diet quality among children in low-income families. Intervention households purchased a 50% subsidized share of local produce and were invited to nine complimentary nutrition classes. The purpose of this study was to assess F3HK reach, dose, and fidelity via a mixed methods process evaluation. Screening and enrollment records indicated reach; study records and postlesson educator surveys tracked dose delivered; CSA pickup logs, lesson sign-in sheets, postseason participant surveys, and postlesson caregiver surveys assessed dose received; and coordinator audits and educator surveys tracked fidelity. Educator interviews contextualized findings. The results of this study were as follows. Reach: enrolled caregivers ( n = 305) were older ( p = .005) than eligible nonenrollees ( n = 243) and more likely to be female ( p < .001). Dose: mean CSA season was 21 weeks (interquartile range [IQR]: 19–23). Median CSA pickup was 88% of the weeks (IQR: 40–100). All sites offered each class at least once. Most adults (77%) and children (54%) attended at least one class; few attended all. Eighty-two percent of caregivers indicated that their household consumed most or all produce. Median lesson activity ratings were 5/5 ("very useful"). Fidelity: CSA locations functioned with integrity to project standards. Educators taught 92% of activities but frequently modified lesson order. This study demonstrates the feasibility of pairing a CO-CSA intervention with nutrition education across geographically dispersed sites. Greater integration of intervention elements and clearer allowance for site-level modifications, particularly for educational elements, may improve intervention dose and, ultimately, impact.